An Atypical Presentation of a Male with Oral-Facial-Digital Syndrome Type 1 Related Ciliopathy - Sheena Sharma; Jennifer M. Kalish; Ethan M. Goldberg; Francis Jeshira Reynoso; Madhura Pradhan (Case Reports in Nephrology)
Background. Oral-facial-digital syndrome type 1 (OFD1) is a rare condition with X-linked dominant inheritance caused by mutations in the Cxorf5 (OFD1) gene. This gene encodes the OFD1 protein located within centrosomes and basal bodies of primary cilia. Approximately 15–50% of patients with OFD1 progress to end-stage kidney disease following development of polycystic changes within the kidneys. This condition almost always causes intrauterine lethality in males. Description of Case Diagnosis and Treatment. A Caucasian male aged 9 years and 9 months presented with increased urinary frequency, increased thirst, and decreased appetite. Physical examination demonstrated short stature, hearing loss, photophobia, murmur, and hypogonadism. He had no other dysmorphic features. Laboratory results revealed anemia, renal insufficiency, and dilute urine with microscopic hematuria but no proteinuria. Ultrasound showed small kidneys with increased echogenicity but no evidence of cystic changes. A Ciliopathy Panel showed a novel and likely pathogenic deletion, approximately 7.9 kb, in the OFD1 gene encompassing exons 16, 17, and 19 (c.1654+833_2599+423del). Brain MRI did not demonstrate typical OFD1 findings. He is currently on chronic hemodialysis awaiting transplant from a living donor. Conclusions. We present a male patient with OFD1 mutation who lacks the classic OFD1 phenotype who presented with end-stage renal disease without evidence of polycystic changes within the kidneys.